"We" are Different: Exploring the Diverse Effects of Friend and Family Accessibility on Consumers' Product Preferences. Issue 3 (15th January 2020) - Fei, Xianzheng; You, Yanfen; Yang, Xiaojing
Abstract : Prior research suggests that close friends and family members exert similar effects on consumer behavior because both represent strong social ties and are subject to communal norms. However, drawing on regulatory focus theory, we postulate that accessibility of friend and family can have divergent impacts on consumers' subsequent purchase decisions. Across four experiments, as well as a pilot study, we demonstrate that accessibility of friend (vs. family) is more likely to activate a promotion focus, which results in more favorable consumer responses toward products with promotion‐focused appeals, whereas accessibility of family (vs. friend) is more likely to activate a prevention focus, which leads to more positive consumer responses toward products with prevention‐focused appeals.